PHYSICAL-MECHANICAL PROPERTIES OF POLYMERIC COMPOSITIONS ON THE BASIS OF POLYIMIDE WITH NANOSTRUCTURES - Voronova, N. A.; Taipova, B. G.; Iskakov, R. M.; Muradov, A. D.; Drobyshev, A. S.; Kupchishin, A. I. (Recent Contributions to Physics, 2009)
In this work physical-mechanical properties of polymeric compositions with nanostructures on the basis of polyimide and montmorillonite radiated with electrons are studied. Polyimide films (PF) with thickness d = 35 mcm and its’ homogeneous compositions with montmorillonite (MM) are researched: 1) PF:MM=99.75%: 0.25% (d = 80 mcm), 2) PF:MM=99.5%:0.5% (d = 90 mcm), 3) PF:MM=99%:1% (d = 70 mcm). polymeric compositions were gained on the basis of polyimide lacquer and montmorillonite solution. Samles were gained in linear electron accelerator ELA-6 in the air in special holders with temperature 25 оС with energy of 2 MeV under average density of flow of beam 0.5 mcA/sm2 and impulse longevity of 5 mcs with it’s repetition rate 200 Gc. Absorbed doses (D) are 50, 100 and 250 kGc. Samples with test portion longevity 50 mm and width 5 mm were deforming in the mode of monoaxial tension until it’s rupture on the automated experimental computer installation. Tests were transacted at temperature 20 ± 2оС and atmospheric moisture capacity 45 ± 5%, pinchers’ speed of separation is 36,09 ± 0,05 mm/sec. Movement of pitchers connected with measuring instrument is no more than 0.1 mm.